Restructuring the ECB - Helge Berger; Jakob de Haan; Robert Inklaar (Center for Economic Studies and ifo Institute (CESifo), 2003)
Soon, euro area membership could more than double, with the vast majority of accession countries being quite different in economic terms compared with current members. Under the current decision-making system, this can lead to high decisionmaking costs and there is a risk that monetary policy could deviate from the targets specified in the Maastricht treaty. While centralization might be a first-best solution to these problems in many ways, there are possible disadvantages from a political economy perspective, including a potential conflict with the established voting rights of current euro area member countries. An alternative solution to ensure the European perspective of decision-making in the ECB Council is to match economic size and voting power. One way to implement this principle is a rotation scheme for national central bank governors that takes economic differences between the member countries into account. The paper discusses various rotation schemes, also with a view to the decision-making cost argument.
Keywords: 330; European Central Bank; centralization of monetary policy; EMU; transition countries; accession countries